Automatización de un fotobiorreactor airlift para la disminución en la concentración de CO2 proveniente de una emisión obtenida por pirolisis de biomasa lignocelulosica. (2021)
The objective of this degree work was to carry out the correct calibration and automation of a laboratory-scale airlift photobioreactor with a sample volume of 3.5 liters, for the cultivation of the microalgae Chlorella sp, and used to retain CO2 from a current emitted by the laboratory muffle. For this, 4 stages were implemented. The first consisted of the bibliographic review of articles and degree projects, to acquire the necessary knowledge both in the programming of the sensors and in the selection of the appropriate instruments, compiling information that allows knowing all the essential parameters for the growth of the microalgae in order to adjust the growth parameters and carry out a control of the CO2 stream, to know its performance with respect to the mitigation of this gas inside the airlift photobioreactor. In the second stage, the sensors were programmed to couple them to the Arduino UNO board. Subsequently, these readings and controls were adjusted using the LabVIEW program which generates graphs that show the control of growth and CO2 elimination that allow knowing all the interaction parameters of the microalgae with the gas injection, and finally, with the fourth stage , use was made of bibliographic tools such as articles referring to this type of reactors and the institutional repository, to know the times, percentages of CO2 decrease and also to observe if this gas stream by bubbling favors the growth of the microalgae under photoautotrophic conditions .